Auranofin, an antirheumatic drug, shows anticancer stem cell potential via suppression of the Stat3 signal - Seung-yeon Ko; Yuna Kim; Jin Sun Chung; Young Bin Kim; Su-lim Kim; Dong-sun Lee; Kyung-hee Chun; Hack Sun Choi (BMB reports, 2025)
Accumulating data have shown that targeting breast cancer stem cells (CSCs) is an auspicious way for anticancer therapies. This study demonstrated that the antirheumatic drug auranofin is a potent CSC inhibitor with anti-CSC action on breast cancer. This research focused on investigating the effect of auranofin on breast cancer and CSCs and its cellular mechanism. Mammosphere formation, colony formation, levels of CD44 high /CD24 low , and aldehyde dehydrogenase 1 expression in the cells were evaluated after auranofin treatment. The anti-CSC properties of auranofin were further examined by gel shift assay and cytokine detection. Auranofin suppressed cell growth, colony formation, migration, and mammosphere formation and triggered apoptosis in breast cancer. Auranofin decreased the CD44 high /CD24 low - and aldehyde dehydrogenase-expressed subpopulations, as well as the Stat3-DNA interaction and phosphorylated Stat3 level. Auranofin also decreased the extracellular levels of interleukin-8 (IL-8) in the mammo-sphere media. Auranofin suppressed the Stat3/IL-8 signal and killed CSCs; therefore, it may be a potential target for CSCs. [BMB Reports 2025; 58(7): 293-299]